การเปรียบเทียบคุณภาพของแบบสอบวินิจฉัยแบบสามระดับสำหรับมโนทัศน์ที่คลาดเคลื่อนทางคณิตศาสตร์ที่ใช้ระดับความมั่นใจที่แตกต่างกัน - อินทร์สวาท, มนัสสิริ; กาญจนวาสี, ศิริชัย (An Online Journal of Education, 2018)
The aims of this study were 1) to develop three-tier diagnostic test of mathematical misconception using different levels of confidence, and 2) to compare quality of the tests using different levels of confidence. The participants were 72 students of the 2015 academic year. The instruments used in the research were 1) three-tier diagnostic tests using two and three levels of confidence and 2) the Thinking Aloud diagnostic test. The data were analyzed by using descriptive statistics, Cramer’s V, the Pearson’s correlation and Cronbach's alpha coefficient. The research findings were as follows: 1) The development of three-tier diagnostic test using two levels of confidence has diagnosed 8 characteristics and three-tier diagnostic test using three levels of confidence has diagnosed 12 characteristics; and 2) The comparisons of quality of the test were as follows: 2.1) the reliability of the former test and the latter test showed no significant differences at 0.5 level; 2.2) the criterion-related validity of the latter test compared with the Thinking Aloud test was higher than the former test; 2.3) the criterion-related validity of the correlation of relationship between content-and-reason answers and confidence answers of the former and the latter showed no significant differences at 0.5 level; 2.4) the average percentages of misconceptions of the former compared with the Thinking Aloud test and the latter showed no significant differences at 0.5 level; and 2.5) the quality of the former and the latter showed no differences.